Vasopressin in the pediatric cardiac intensive care unit: Myth or reality - Singh Vishal; Sharma Rajesh; Agrawal Amit; Varma Amit (Wolters Kluwer Medknow Publications, 2009)
Pediatric cardiac surgery is undergoing a metamorphosis, with more and more critical patients being operated in our country today. Although the principles of physiology have not changed, it is imperative that care providers continue to stay abreast with developments and newer drugs that may help modify the outcome. The team dynamics have also become more complex, which necessitates the need for all care providers (surgeons, cardiologists, anesthesiologists, and intensivists) to better understand the interactions and benefits of newer drugs. Vasopressin has been used in our adult patients for more than a decade and recently has found its rightful place in the pediatric armoury. The objective of this article is to review the physiology of vasopressin and the rationale of its use in critically ill children with shock, in context of the available published data.